Coverage bias of Bangladesh television media: a portrayal of power and politics - Islam, Sheikh Mohammad Shafiul (Penerbit Universiti Kebangsaan Malaysia, 2016)
After the fall of autocratic regime of military ruler in 1990, the political governments in Bangladesh has created platform of media expansion through ‘privatization policy’. The only state-run Bangladesh Television (BTV) was in operation till mid-1990s but the number of privately owned satellite channels has rose to a few dozens, at present. This growth is perceived abnormal in terms of role and professionalism of the channels to the society since their affiliation with the political parties is critically viewed for managing license. This study aims to explore the coverage bias of the TV channels through analyzing the contents of 130 reports selected purposively from three TV channels, both the state-run and corporate owned. It reveals that 51 reports (39%) concentrated on power, politics and elites; the highest thematic coverage by the selected channels. The ruling party got the highest coverage where the Prime Minister, Ministers, Members of the Parliament and the senior political leaders were projected with importance. The reports were mostly male dominated and urban focused. Thus, the television channels portrayed the powerful and influential classes neglecting the common people who represent an empire of the dominant classes in Bangladesh.